The impact of vegan diet for 21 days on blood uric acid level in adults - Alvina Putri Tjan; Fitriyani Nasution (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
One of the risk factors for hyperuricemia is consumption of purine-rich foods. Plant-based sources, such as nuts and legumes, have high amount of purine, in which it is commmonly consumed by vegan’s. The aim of this study is to examine the impact of vegan diet for 21 days on serum uric acid (UA) levels. This research used cross-sectional design. Data were collected from secondary data in Jingsi Books and Café, from October 2021 until January 2022. The population of the study is derived from 21 days vegan diet program by Tzu Chi Buddhist Association with total sample of 95 by using total sampling method. The data in this study is grouped according to age (<50 and ≥50 years old), gender, and both. The statistical test that is used is paired T-tests. The results showed that serum UA (mg/dl) increased in female (both age groups) and male <50 years old with increased mean 0,3, 0,2, and 0,4. For male aged ≥50 years old, there’s reduction in serum UA with reduction mean 0,1. The result is clinically significant with p-value 0,001. In conclusion, 21-day vegan diet increases serum UA levels in all populations, except for male ≥50 years old.